Judicial Performance Review in Arizona: A Critical Assessment - Rebecca White Berch; Erin Norris Bass (Oñati Socio-Legal Series)
Judicial performance evaluations are a relatively new tool for assessing judges and providing information to voters to help them determine whether to retain judges in contested or retention elections. Arizona implemented its judicial evaluation program about 20 years ago, and since that time, the state has continually strived to improve its process. The result is that today Arizona has one of the most progressive and comprehensive judicial performance evaluation programs in the United States. This article takes a critical look at the strengths and weaknesses of Arizona’s program, keeping in mind two key values that the system seeks to protect: judicial accountability and judicial independence.